Molecular and cytogenetic studies of the Prader-Willi syndrome. Issue 10 (October 1991) - Trent, R J; Volpato, F; Smith, A; Lindeman, R; Wong, M K; Warne, G; Haan, E
Abstract : Twenty-seven subjects with the Prader-Willi syndrome (PWS) were studied. Sixteen (59%) had a cytogenetic deletion involving chromosome 15q11-13. Nine were non-deletional and two patients had structural rearrangements of chromosome 15: 47, XY, + del(15)(pter—-q12), var(15)(p11) and 45, XX, t(14q15q). At the DNA level, a greater proportion of patients (74%) showed loss of one chromosome 15q11-13 allele using a combination of densitometry and RFLP analysis. Deletion sizes were variable with 13 of 20 detectable both cytogenetically and with probe pML34 (D15S9). The remaining seven had microdeletions at the pML34 locus. Heterogeneity was further seen in three subjects who had cytogenetic deletions but normal DNA studies. In one patient there was evidence of a duplication at the pML34 locus. A new molecular rearrangement was identified with probe p3.21 (D15S10) in two patients and their mothers. Fifteen family studies were performed. In all 10 families where there was a molecular deletion, this was shown to have arisen de novo. DNA mapping confirmed that the paternal 15q allele was lost in three patients with PWS.